The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1515/jpem.2000.13.s1.787
|View full text |Cite
|
Sign up to set email alerts
|

Near Final Height after GnRH Agonist Treatment in Central Precocious Puberty

Abstract: The impact of treatment of central precocious puberty (CPP) with gonadotropin-releasing hormone agonists (GnRHa) on final height remains controversial. We analyzed the long term results of 23 girls with CPP treated with triptorelin or leuprolide. Their "near final height" (NFH) assessed at a bone age of at least 14 years and expressed as SDS, was compared either with predicted height before treatment (PAH) or with parental height (TH). We also compared NFH of 12 girls treated before 8 years of age (7.0 +/- 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 9 publications
0
14
0
2
Order By: Relevance
“…Although no difference in FH between TR- and LA-treated girls was observed by Micillo et al [25], Lanes et al [19] recently reported that FH increased a mean 5.5 ± 1.3 cm over PAH in LA-treated CPP patients, while it increased 8.7 ± 2.2 cm in the TR-treated group. BA advanced 1.8 ± 0.4 years over a 2.8-year treatment period in the LA-treated group, while it advanced 1.5 ± 0.3 years in the TR-treated patients over 2.5 years of treatment, yielding no significant difference in bone maturation between GnRHa treatments [19].…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Although no difference in FH between TR- and LA-treated girls was observed by Micillo et al [25], Lanes et al [19] recently reported that FH increased a mean 5.5 ± 1.3 cm over PAH in LA-treated CPP patients, while it increased 8.7 ± 2.2 cm in the TR-treated group. BA advanced 1.8 ± 0.4 years over a 2.8-year treatment period in the LA-treated group, while it advanced 1.5 ± 0.3 years in the TR-treated patients over 2.5 years of treatment, yielding no significant difference in bone maturation between GnRHa treatments [19].…”
Section: Discussionmentioning
confidence: 86%
“…Partsch et al [26] reported that initial BA advancement and treatment duration were factors that explained 68% of the variability of Ht gain, while growth after GnRHa withdrawal had no significant predictive effect on the FH. Others found that average growth rate during GnRHa treatment mainly affected Ht gain at treatment withdrawal which positively correlated to FH [24,25,26]. In our series, significant Ht difference between TR and LA treatments was achieved during but not after GnRHa treatment: similar further ΔHt increment (around 9.0 cm) after GnRHa withdrawal to FH was observed in both spCPP groups (p > 0.05; LA vs. TR group; data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Porém, a experiência dos diversos grupos quanto à eficiência do tratamento na recuperação da perda estatural é bastante discrepante (25)(26)(27)(28)(29)(30). Diferenças nos resultados observados são devidas a variações das características de cada casuística, diferentes critérios de diagnóstico, idade de início e duração do tratamento, tipo de análogo empregado e variável critério para a suspensão do tratamento.…”
Section: Resultados Com O Uso De Gnrhaunclassified
“…The compromised final height and early onset of secondary sex changes tend to bring a number of psychological and behavioral issues [2] . Gonadotropin-releasing hormone agonists (GnRH-a) injected intra-muscularly every four weeks, has been widely used worldwide to suppress the secretion of sex hormones and accordingly, delay sexual development and epiphyseal fusion, resulting in elevating the adult height, as well as benefit probably psychosocial disturbances related to sexual development [3][4][5][6][7] . However, the cost and sharp pains on injection sites decline its adherence by both children and their family.…”
mentioning
confidence: 99%